Towards a unification of independent particle and collective models - Anagnostatos, G. S. (HNPS Advances in Nuclear Physics, 2020)
A unification of Independent Particle and Collective Models is proposed via the Isomorphic Shell Model. Through this model, based on fundamental properties of fermions, an average shape for each nucleus is derived which simultaneously reproduces independent particle and collective properties. 20Ne is taken as an example.